2020
DOI: 10.3390/toxins12050309
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing Cancer Drugs Batimastat and Marimastat to Inhibit the Activity of a Group I Metalloprotease from the Venom of the Western Diamondback Rattlesnake, Crotalus atrox

Abstract: Snakebite envenomation causes over 140,000 deaths every year, predominantly in developing countries. As a result, it is one of the most lethal neglected tropical diseases. It is associated with incredibly complex pathophysiology due to the vast number of unique toxins/proteins present in the venoms of diverse snake species found worldwide. Here, we report the purification and functional characteristics of a Group I (PI) metalloprotease (CAMP-2) from the venom of the western diamondback rattlesnake, Crotalus at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 45 publications
1
46
0
Order By: Relevance
“…The results of this study show that these compounds are capable of neutralizing the coagulopathic activities of individual toxins present in the venoms of a number of Viperinae species. While this is consistent with previous work on small molecule inhibitors and chelators that exhibit anti-hemorrhagic and anti-procoagulant activities of snake venoms [ 9 , 20 , 23 , 42 , 43 , 60 ], here we have studied the relative neutralization potencies of these small molecules on individual coagulopathic venom toxins. Our findings reveal that varespladib is not only effective against the activity of anti-coagulant PLA 2 toxins, but also shows some inhibitory activity against procoagulant venom toxins.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results of this study show that these compounds are capable of neutralizing the coagulopathic activities of individual toxins present in the venoms of a number of Viperinae species. While this is consistent with previous work on small molecule inhibitors and chelators that exhibit anti-hemorrhagic and anti-procoagulant activities of snake venoms [ 9 , 20 , 23 , 42 , 43 , 60 ], here we have studied the relative neutralization potencies of these small molecules on individual coagulopathic venom toxins. Our findings reveal that varespladib is not only effective against the activity of anti-coagulant PLA 2 toxins, but also shows some inhibitory activity against procoagulant venom toxins.…”
Section: Discussionsupporting
confidence: 89%
“…SVMPs are toxins that are structurally and functionally homologous to matrix metalloproteinses [38][39][40]. Like other compounds in this class of drugs (e.g., batimastat [41]), marimastat is a promising drug candidate for treating snakebite due to its inhibitory capabilities against SVMP toxins [42,43]. Marimastat was found to effectively inhibit the hemorrhagic, coagulant and defibrinogenating effects and proteinase activities induced by Echis ocellatus venom [42].…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the most notable of these is the PLA 2 -inhibitor, varespladib, which has been widely explored for repurposing as a snakebite therapy, and has shown substantial promise in preclinical models against a number of elapid and viper venoms 22 , 26 , 27 , 29 . In addition, several SVMP-inhibitors have been demonstrated to be capable of abolishing venom-induced hemorrhage or dermonecrosis, including metal ion chelators 21 , 24 , 25 , 28 and peptidomimetic hydroxamate inhibitors 23 , 24 , 30 . We recently reported that 2,3-dimercapto-1-propanesulfonic acid (DMPS), a Zn 2+ chelator that is a licensed oral medicine used to treat heavy metal poisoning, was particularly effective in preclinically neutralizing both the local and systemic toxicity of Zn 2+ -dependent SVMP-rich saw-scaled viper venoms (genus Echis ) 28 .…”
Section: Introductionmentioning
confidence: 99%
“…PLA 2 s are components of many venoms and produce significant pathological effects. Similarly, batimastat and marimastat are broad-spectrum matrix metalloprotease inhibitors which have been demonstrated to reduce the destructive effects of snake venom metalloproteases (SVMPs) [25,26]. A preliminary report of a combination of varespladib and marimastat, showed promise in an in vivo mouse model of SBE.…”
Section: Discussionmentioning
confidence: 99%